Modulating high-energy visible light absorption to attain neutral-state black electrochromic polymers. Issue 1 (23rd November 2015) - Neo, Wei Teng; Cho, Ching Mui; Shi, Zugui; Chua, Soo-Jin; Xu, Jianwei
Abstract : Neutral-state black electrochromic polymers were achieved by incorporating an additional donor to enhance the blue-absorption. Abstract : Neutral-state black diketopyrrolopyrrole (DPP)-based conjugated polymers with the colour channels a * from −3 to 0 and b * from −2 to −7 are achieved by incorporating an additional donor segment – dialkoxythiophene (DalkOT), which leads to the enhancement in blue-wavelength absorption. The polymers display black-to-transmissive grey electrochromic switching with good redox stability.